Development and validation of the Subjective Recovery Assessment Scale for patients with schizophrenia. Issue 2 (3rd April 2018) - Yildiz, Mustafa; Erim, Rahsan; Soygur, Haldun; Tural, Umit; Kiras, Fatma; Gules, Emrah
ABSTRACT: OBJECTIVE: Studies investigating the recovery from schizophrenia revealed two concepts of recovery; one is clinical recovery, and the other is personal or subjective recovery. Both states of recovery require specific assessment tools and therapeutic approaches. While current measures of clinical recovery can be used upon consensus all over the world, measures of subjective recovery which are based on cultural and individual values are yet to be investigated. The aim of this study was to develop and validate the Subjective Recovery Assessment Scale (SubRAS) for patients with schizophrenia. METHODS: The SubRAS consisting of 17-item was prepared using related literature with focus group interviews. Internal consistency reliability was assessed by Cronbach's alpha coefficients, and test–retest reliability was assessed. Exploratory factor analyses and correlations with Global Assessment of Functioning (GAF), The Heinrichs-Carpenter Quality of Life Scale (QLS), Positive and Negative Syndrome Scale (PANSS), and Clinical Global Impression – Severity (CGI-S) were used to examine the factor-based validity and construct validity of the SubRAS. RESULTS: The participants consisted of 127 patients with schizophrenia ( n  = 110) and schizoaffective disorder ( n  = 17), with 63.6% being male and a mean age of 41.2 years. Cronbach's alpha coefficient of the scale was calculated as 0.98 while item-total score correlation coefficients were measured between 0.83 and 0.94. Test–retest reliability ( r  = .98) was very satisfactory. As for construct validity, a one-factor solution was obtained that could explain 83.0% of the variance. The scale showed a high correlation with the GAF ( r  = .82), the QLS ( r  = .76), PANSS ( r  = −.74), and CGI-S ( r  = −.74). CONCLUSIONS: SubRAS is a valid and reliable instrument that can be utilized for patients with schizophrenia to assess their subjective recovery states. It is a culture-sensitive self-assessment instrument and easy to use for Turkish patients with schizophrenia.